(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
The process of adaptation of the Crimean Tatars deported to Central Asia to Turkestan is clearly visible from the second half of the 19th century. In particular, initially the Crimean Tatars visited the khanates of Central Asia for trade purposes, but later, starting from the second half of the 19th century, the military administrators of the Russian Empire used them as interpreters and translators in the conquest of Turkestan, and, if necessary, as military officers. used In particular, the 19th century created an opportunity for the Crimean Tatars to study and occupy the markets of Central Asia. This article reveals the source science of the history of the Crimean Tatars deported to Central Asia and its current historical significance.